АДМИНИСТРАТИВНО-ПРАВОВОЙ СТАТУС НАЦИОНАЛЬНОЙ ПОЛИЦИИ УКРАИНЫ: СРАВНИТЕЛЬНО-ПРАВОВОЙ АСПЕКТ - ПРИПУТЕНЬ, Дмитрий Сергеевич (SUPREMANCE OF LAW, 2016)
Article is devoted to administrative and legal status of the National Police of Ukraine. There is noted the definition of administrative and legal status and its constituent elements. In this article administrative and legal status of the National Police of Ukraine can be defined as a system of interconnected components, allowing to define the subject of conduct, responsibilities, tasks and functions of the police (as well as a some other elements) by using administrative law norms. Is proposed to allocate such constituent elements of the administrative and legal status of the National Police of Ukraine as: a) the subject of conduct; 2) tasks and functions; 3) the rights and responsibilities. The National Police of Ukraine subject conduct is protection of human rights and freedoms, combating crime and ensuring of public order and safety. Police activities shall be based on the clearly defined in law principles. The attention is focused on the subject of conduct and main tasks of the police in some of European Union member states. Considered by foreign legislation about police at a sufficient level, defines it’s administrative and legal status. Th ere was a simplicity of presentation standards and less detail on certain moments, which simplifi es the perception of such legislation as a whole. Considerable attention is paid to international police cooperation and collaboration with the authorities of the public administration, community and other institutions. It was concluded about relevance of using foreign experience in order to optimize the main tasks and functions of the National Police of Ukraine.